2021
DOI: 10.3390/biomedicines9040347
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulating Hippo-YAP Signaling in Liver Cancer

Abstract: Liver cancer is one of the most common cancers worldwide, and its prevalence and mortality rate are increasing due to the lack of biomarkers and effective treatments. The Hippo signaling pathway has long been known to control liver size, and genetic depletion of Hippo kinases leads to liver cancer in mice through activation of the downstream effectors yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ). Both YAP and TAZ not only reprogram tumor cells but also alter the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…Using bioinformatics approaches, we identified that Nf2 (Neurofibromin 2) is a predicted target of miR-122. NF2 is known as a key component in the HIPPO signaling cascade, the major regulator of organ size/growth ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ). Upon acute tissue injuries, such as liver resection, NF2 no longer mediates YAP/TAZ (Yes-associated protein and transcriptional coactivator with PDZ-binding motif) complex phosphorylation and allows its recruitment to the nucleus, where it functions as a transcription factor for repair and regeneration processes ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using bioinformatics approaches, we identified that Nf2 (Neurofibromin 2) is a predicted target of miR-122. NF2 is known as a key component in the HIPPO signaling cascade, the major regulator of organ size/growth ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ). Upon acute tissue injuries, such as liver resection, NF2 no longer mediates YAP/TAZ (Yes-associated protein and transcriptional coactivator with PDZ-binding motif) complex phosphorylation and allows its recruitment to the nucleus, where it functions as a transcription factor for repair and regeneration processes ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF2 is known as a key component in the HIPPO signaling cascade, the major regulator of organ size/growth ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ). Upon acute tissue injuries, such as liver resection, NF2 no longer mediates YAP/TAZ (Yes-associated protein and transcriptional coactivator with PDZ-binding motif) complex phosphorylation and allows its recruitment to the nucleus, where it functions as a transcription factor for repair and regeneration processes ( Lee et al, 2021 ; Nguyen-Lefebvre et al, 2021 ). At baseline conditions, HF-O had lower hepatic miR-122 levels, while Nf2 gene expression was upregulated, which is an additional indicator that miR-122 can act as an Nf2 repressor.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway has two associated transcriptional co-activators, YES-associated protein 1 (YAP) and TAZ (or WWRT1), which are activated by the ECM and thus serve as a central regulator of cell proliferation, which can regulate the growth and development of tissue ( 94 , 95 ). It was found that pulmonary vascular stiffness can activate YAP/TAZ at early PH, thus inducing the Mir-130/301 family to further enhance ECM remodeling and cell proliferation in vivo ( 96 , 97 ). In addition, YAP/TAZ-induced pulmonary vascular stiffness has also been found to control important metabolic changes in PH ( 17 , 92 ).…”
Section: Glutamine Metabolism In Pulmonary Hypertensionmentioning
confidence: 99%
“…In summary, YAP1-mediated resistance to therapy typically includes an initial upregulation of YAP1 activity. This upregulation may result from the inactivation of the NF2-Hippo axis via mechanisms such as genetic alterations (for example, of the NF2 and LATS1/2 genes), inhibition of LATS kinases through RhoA signaling or downregulation of LATS/ upregulation of YAP1 mRNA via micro RNAs [56,57]. Additionally, YAP1 activation may come from signals increasing YAP1 gene expression, protein half-life or nuclear translocation.…”
Section: Yap1 As a Mechanism Of Intrinsic And Acquired Drug Resistancementioning
confidence: 99%